EFEK PEMASARAN DAN PERAN KELUARGA DALAM PEMBENTUKAN EKUITAS MEREK - Siane Ivana Hartanto; MF. Shellyana Junaedi (Program Magister Manajemen STIE Widya Wiwaha Yogyakarta, 2017)
This study aims to determine wheter the ads and family’s effect in the form of brand awareness and brand association and how the advertising, price promotions, and family influence in shaping the perception of quality. Brand awareness, brand associations, and perceived quality will also be tested the significant effect directly and indirectly the brand equity through brand loyalty. This research was conducted in the Yogyakarta where respondents are students. This study uses a quantitative method by distributing questionnaires to 200 respondents. Data retrieval technique using purposive sampling. Data processing techniques using regression analysis. The results of this study indicate that advertising and family has significant effects positively on brand awareness, but only a significant effect of family on brand association. Advertisements, family and the price also proved significant effect on the perception of quality. Brand awareness, brand associations and perceived quality have a significant effect directly or indirectly on brand equity through brand loyalty.